Understanding Effectiveness of International Sanctions - Thomas Biersteker (Vestnik MGIMO-Universiteta)
Thomas Biersteker took part in 2019 Gerda Henkel Forum: Values and Interests in Communication Between Russia and The West held in MGIMO-University in late April this year and on the margins of the Forum he was kind enough to give an interview to our editor Vadim Belenkov on effectiveness of targeted international sanctions. Professor Biersteker is a renowned expert on this issue, he co-edited a book «Targeted Sanctions» recently published by Cambridge University Press. The interview shows that targeted sanctions involve restrictive measures against a narrowly-defined range of individuals and firms. Professor Biersteker explained in detail the difference between sanctions with the purpose of coercion, constraining and signaling. He reaffirmed his claim that effectiveness of sanctions should be studied separately for each type of purposes. In the interview professor Biersteker updated some of the findings published in his book three years ago. In 2016 constraining and signaling sanctions were effective at the same level, 27 % of the time. Today data reveal that effective constraining fell by 4 % points and effective signaling rose by 2 % points. Effectiveness of coercion remains at 10 %. The average effectiveness of sanctions across three types is about 20 %. Taking into consideration the difficulty of conflicts and issues over which sanctions are applied – North Korea’s nuclear program, Iran’s potential development of nuclear weapon program, ethnic and religious conflicts in Africa, the Middle East – 20 % should not be considered a small figure. Biersteker also reaffirmed the «sanctions paradox» found in 1999 by Daniel Drezner that very often the countries against which sanctions would be most likely effective are those that are most interdependent whereas sanctions are usually applied in situations when they are less likely to be effective.